Atypical Presentation of Acute Myocardial Infarction (Journal of Medicine, 2021)
Introduction: Chest pain has been reported as the cardinal clinical feature of Acute Myocardial Infarction (AMI). However, a substantial number of patients may have atypical or no symptoms on initial evaluation. The absence of typical chest pain and the vagueness of symptoms might result in a delay in seeking medical care. In this study atypical presentations of AMI and in-hospital mortality and outcome were evaluated.Material and Methods: A hospital based cross sectional study was performed among 110 patients of AMI admitted in the CCU who fulfilled the inclusion criteria. The Study was done from July, 2013 to January, 2014 in Dhaka Medical College Hospital, Dhaka, and National Institute of Cardiovascular Diseases (NICVD), Dhaka.Results: Among the 110 patients with AMI, 22 (20%) patients presented with atypical presentation. The maximum incidence of AMI with atypical presentations was in the age group of 65-74 years (28.57%). Dyspnoea (36.36%) was the most among the atypical symptom followed by vomiting 22.72% and the least incident with vertigo 4.54%. Inferior MI being the highest 46% among atypical MI where as mortality rate was high among the antero-septal MI (22.86%). The in hospital mortality of myocardial infarction patients who presented with typical and atypical symptoms were 15% and 36.36 %.Conclusion: The patients without chest pain represent a substantial segment of the MI population. Older patients presented with more atypical symptoms with breathlessness being the commonest atypical symptoms. Mortality was high among the patients who presented with atypical symptoms, increasing age, and who presented lately.J MEDICINE 2021; 22: 88-94